2022
DOI: 10.1108/lht-01-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

The scientific outcome in the domain of grey literature: bibliometric mapping and visualisation using the R-bibliometrix package and the VOSviewer

Abstract: PurposeThe current study aims to map the scientific output of grey literature (GL) through bibliometric approaches.Design/methodology/approachThe source for data extraction is a comprehensive “indexing and abstracting” database, “Web of Science” (WOS). A lexical title search was applied to get the corpus of the study – a total of 4,599 articles were extracted for data analysis and visualisation. Further, the data were analysed by using the data analytical tools, R-studio and VOSViewer.FindingsThe findings show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Educational resources and open-access repositories can also include teaching materials, such as lectures, lesson plans and course materials. Grey literature includes reports, working papers and other publications that are not formally published or peer-reviewed but are still of interest to researchers (Wani and Ganaie, 2022). Table 4 highlighted that journal articles (3,005, 22.13%) are the main content type in OARs in the field of “technology” followed by thesis and dissertations (2,745, 20.22%), books, chapters and sections (1,680, 12.37%).…”
Section: Resultsmentioning
confidence: 99%
“…Educational resources and open-access repositories can also include teaching materials, such as lectures, lesson plans and course materials. Grey literature includes reports, working papers and other publications that are not formally published or peer-reviewed but are still of interest to researchers (Wani and Ganaie, 2022). Table 4 highlighted that journal articles (3,005, 22.13%) are the main content type in OARs in the field of “technology” followed by thesis and dissertations (2,745, 20.22%), books, chapters and sections (1,680, 12.37%).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding research trends, Wani and Ganaie (2024) conducted a bibliometric analysis and found the publication of gray literature, information produced outside of traditional publishing and distribution channels, has been increasing recently, with prominent sources like PLOS One…”
Section: Current Research Trendsmentioning
confidence: 99%
“…Regarding research trends, Wani and Ganaie (2024) conducted a bibliometric analysis and found the publication of gray literature, information produced outside of traditional publishing and distribution channels, has been increasing recently, with prominent sources like PLOS One and NeuroImage. Yan et al (2024) provide a systematic knowledge map for researchers in the field of research data management and found that collaboration between scholars and institutions is weak.…”
Section: Current Research Trendsmentioning
confidence: 99%
“…Readers may be interested in some related articles on whether authors play fair or manipulate Google Scholar bibliometric indicators, such as h-index and i10-index (Loan and Shah, 2022), and the analysis of Sci-Hub use with Google Trends (Behboudi et al ., 2021); Chen et al . (2021) studied the effect of interdisciplinary components' citation intensity on scientific impact, whether proceedings papers in science fields have higher impacts than those in social science and humanities (Yang and Qi, 2021), characteristics analysis and evaluation of discourse leading for academic journals (Wang, 2022), the ecosystem of research tools for scholarly communication (Rao et al ., 2022), the scientific outcome in the domain of grey literature (Wani and Ganaie, 2022), early discovering highly cited academic papers (Tang et al ., 2023) and textbook citations (Maleki et al ., 2023).…”
Section: Bibliometric Analytics For Academic Rankingmentioning
confidence: 99%